Developing an integrated urban farming management framework: A mixed-method study informed by the theory of planned behaviour - Faghiri, Hamed; Yusop, Zulkornain; Mohamed, Zainal Abidin (International Journal of Accounting, Finance and Business, 2025)
Urban farming is increasingly recognized as a strategic response to rising food insecurity, environmental degradation, and socio-economic pressures in rapidly urbanizing regions. Despite expanding interest, adoption remains limited due to behavioural, institutional, and management-related challenges. This study proposes the Integrated Urban Farming Management Framework (IUFMF), developed through the combination of the Theory of Planned Behaviour (TPB) and mixed-method evidence. The qualitative phase, involving semi-structured interviews with 50 urban citizens, identified behavioural determinants, operational requirements, and socio-economic drivers of urban farming participation. These findings informed a quantitative survey administered to 200 respondents across major cities, with Partial Least Squares Structural Equation Modelling (PLS-SEM) confirming that awareness, non-monetary benefits, monetary incentives, and personal interest significantly increase willingness to venture into urban farming, while barriers showed no significant effect. Findings from both approaches were integrated into a five-layer IUFMF comprising: Empowerment, Support, Method, Technology, and Outcome. The framework positions empowerment through knowledge, training, and awareness as the behavioural foundation, followed by institutional and policy-based support systems, resource-efficient farming methods, technology integration, and long-term sustainability outcomes. By merging behavioural intention with practical implementation pathways, the IUFMF offers a scalable and adaptable structure for strengthening urban farming systems. This research contributes theoretically by extending TPB within high-density urban agriculture contexts, and practically by providing a structured model to guide policymakers, practitioners, and communities in designing effective and sustainable urban farming strategies.